Technology Refusal - Hodas, Steven (Education Policy Analysis Archives, 1993)
Analyses of the deployment of technology in schools usually note its lack of impact on the day-to-day values and practices of teachers, administrators, and students. This is generally construed as an implementation failure, or as resulting from a temperamental shortcoming on the part of teachers or technologists. It is predicated on the tacit assumption that the technology itself is value-free. This paper proposes that technology is never neutral: that its values and practices must always either support or subvert those of the organization into which it is placed; and that the failures of technology to alter the look-and-feel of schools more generally results from a mismatch between the values of school organization and those embedded within the contested technology.